Wezbrania na Bobrze w Żaganiu w świetle obserwacji historycznych = Flood situations on the Bober river in Żagań city, in the light of historic observations - Kołodziejczyk, Urszula; Kuroczycki, Lech; Żebrowska, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article it was presented information about the biggest spring-summer swelling in the Bóbr in Żagań in XIX, XX and XXIst centuries. Based on hydrological data it was stated, that the flood situations in the Bóbr river basin appear every 3-5 years being the characteristic feature of the climate of Poland. Straining the rain and its spatial distribution are deciding on the flood situations.
Keywords: wezbrania powodziowe; Bóbr (rzeka); Żagań; flood situation